Peningkatan Motivasi Berprestasi Siswa SMA melalui Cognitive Behavior Counseling Teknik Self-instruction dan Self-monitoring - Prio Utomo; Adi Atmoko; Imanuel Hitipeuw (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This study aimed at improving the achievement motivation of high school students using cognitive behaviour counselling with self-instruction and self-monitoring techniques; and to knowing the difference of effectiveness between the two techniques given. The experimental research with the pretest-posttest two treatment designs was used as a research design. Data were collected using the treatment materials and the achievement motivation scale. Data were analysed by the descriptively and statistically (Wilcoxon test and The Mann-Whitney U test). The results of this study showed that there was an increasing in achievement motivation of high school students after being given counselling with self-instruction and self-monitoring techniques; and there was no significant difference between the two techniques to increase the achievement motivation of high school students.  Abstrak: Penelitian ini bertujuan untuk meningkatkan motivasi berprestasi siswa SMA melalui cognitive behavior counseling teknik self-instruction dan self-monitoring; untuk mengetahui perbedaan efektivitas kedua teknik yang diberikan. Experimental research dengan the pretest-posttest two treatment designs digunakan sebagai rancangan penelitian. Pengumpulan data menggunakan bahan perlakuan dan skala motivasi berprestasi. Data dianalisis secara deskripstif dan statistik (uji Wilcoxon dan uji The Mann-Whitney U test). Hasil penelitian menunjukkan, terdapat peningkatan motivasi berprestasi siswa secara signifikan setelah diberi konseling teknik self-intruction dan self-monitoring; tidak terdapat perbedaan dari kedua teknik terhadap peningkatan motivasi berprestasi siswa SMA.